2019
DOI: 10.1186/s13256-019-2014-y
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy after an upper and lower endoscopy: a case report and review of the literature

Abstract: BackgroundGastrointestinal endoscopies are safe and follow guidelines that emphasize patient care.Although adverse outcomes are rare, high-risk patients may be predisposed to certain events.Case presentationWe report a unique case of a Caucasian woman with takotsubo cardiomyopathy following an upper and lower endoscopy.ConclusionsOur report suggests the importance of understanding possible endoscopic complications in patients who may experience stress cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(43 reference statements)
1
4
0
1
Order By: Relevance
“…To the best of our knowledge, at least eight cases of TTS related to flexible bronchoscopy have been reported in the English literature 4 ) . This number is approximately the same as the number of cases reported to have developed after upper and lower gastrointestinal endoscopy 5 ) . Considering the frequency with which each test is performed in routine practice, the risk of developing TTS may be higher with bronchoscopy than with gastrointestinal endoscopy, although the exact incidence of endoscopy-related TTS is unknown.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…To the best of our knowledge, at least eight cases of TTS related to flexible bronchoscopy have been reported in the English literature 4 ) . This number is approximately the same as the number of cases reported to have developed after upper and lower gastrointestinal endoscopy 5 ) . Considering the frequency with which each test is performed in routine practice, the risk of developing TTS may be higher with bronchoscopy than with gastrointestinal endoscopy, although the exact incidence of endoscopy-related TTS is unknown.…”
Section: Discussionsupporting
confidence: 57%
“…Considering the frequency with which each test is performed in routine practice, the risk of developing TTS may be higher with bronchoscopy than with gastrointestinal endoscopy, although the exact incidence of endoscopy-related TTS is unknown. The clinical course of patients with endoscopy-induced TTS was generally favorable, except for frail elderly patients with complications 4 , 5 ) . However, Gili et al reported that CA was observed in 8.1% of patients with TTS, of whom 81.6% had CA at the initial presentation of TTS, and they showed worse outcomes compared to patients without CA 6 ) .…”
Section: Discussionmentioning
confidence: 94%
“…It is also known as stress cardiomyopathy, broken heart syndrome, or apical ballooning syndrome. In this condition, the echocardiogram shows diffuse wall motion abnormalities with impaired LVSD in absence of coronary artery disease [2]. TCM was first described by Japanese scientists in 1991, and the name was given to it in view of the distinctive echocardiographic resemblance to traditional takotsubo, or octopus fishing pots [3].…”
Section: Introductionmentioning
confidence: 99%
“…С учетом появления этих изменений было принято решение о проведении коронароангиографии для исключения возможного коронарного тромбоза и проведения стентирования. Однако при анализе коронарограмм признаков гемодинамически значи-стрессовой фактор, возникающие лабораторноинструментальные изменения, как правило, обратимы [1]. Согласно литературным обзорам, заболевание является редким, его распространенность составляет от 0,02% до 2% пациентов, госпитализированных в стационар с направительным диагнозом острого коронарного синдрома [2].…”
Section: Introductionunclassified